Answer:
(a) If f and t are both even functions, product ft is even.
(b) If f and t are both odd functions, product ft is even.
(c) If f is even and t is odd, product ft is odd.
Step-by-step explanation:
Even function: A function g(x) is called an even function if
![g(-x)=g(x)](https://tex.z-dn.net/?f=g%28-x%29%3Dg%28x%29)
Odd function: A function g(x) is called an odd function if
![g(-x)=-g(x)](https://tex.z-dn.net/?f=g%28-x%29%3D-g%28x%29)
(a)
Let f and t are both even functions, then
![f(-x)=f(x)](https://tex.z-dn.net/?f=f%28-x%29%3Df%28x%29)
![t(-x)=t(x)](https://tex.z-dn.net/?f=t%28-x%29%3Dt%28x%29)
The product of both functions is
![ft(x)=f(x)t(x)](https://tex.z-dn.net/?f=ft%28x%29%3Df%28x%29t%28x%29)
![ft(-x)=f(-x)t(-x)](https://tex.z-dn.net/?f=ft%28-x%29%3Df%28-x%29t%28-x%29)
![ft(-x)=f(x)t(x)](https://tex.z-dn.net/?f=ft%28-x%29%3Df%28x%29t%28x%29)
![ft(-x)=ft(x)](https://tex.z-dn.net/?f=ft%28-x%29%3Dft%28x%29)
The function ft is even function.
(b)
Let f and t are both odd functions, then
![f(-x)=-f(x)](https://tex.z-dn.net/?f=f%28-x%29%3D-f%28x%29)
![t(-x)=-t(x)](https://tex.z-dn.net/?f=t%28-x%29%3D-t%28x%29)
The product of both functions is
![ft(x)=f(x)t(x)](https://tex.z-dn.net/?f=ft%28x%29%3Df%28x%29t%28x%29)
![ft(-x)=f(-x)t(-x)](https://tex.z-dn.net/?f=ft%28-x%29%3Df%28-x%29t%28-x%29)
![ft(-x)=[-f(x)][-t(x)]](https://tex.z-dn.net/?f=ft%28-x%29%3D%5B-f%28x%29%5D%5B-t%28x%29%5D)
![ft(-x)=ft(x)](https://tex.z-dn.net/?f=ft%28-x%29%3Dft%28x%29)
The function ft is even function.
(c)
Let f is even and t odd function, then
![f(-x)=f(x)](https://tex.z-dn.net/?f=f%28-x%29%3Df%28x%29)
![t(-x)=-t(x)](https://tex.z-dn.net/?f=t%28-x%29%3D-t%28x%29)
The product of both functions is
![ft(x)=f(x)t(x)](https://tex.z-dn.net/?f=ft%28x%29%3Df%28x%29t%28x%29)
![ft(-x)=f(-x)t(-x)](https://tex.z-dn.net/?f=ft%28-x%29%3Df%28-x%29t%28-x%29)
![ft(-x)=[f(x)][-t(x)]](https://tex.z-dn.net/?f=ft%28-x%29%3D%5Bf%28x%29%5D%5B-t%28x%29%5D)
![ft(-x)=-ft(x)](https://tex.z-dn.net/?f=ft%28-x%29%3D-ft%28x%29)
The function ft is odd function.